BUDAYA PALEOLITIK PEGUNUNGAN SERAYU DI WILAYAH KABUPATEN BANYUMAS - Hidayat, Muhammad (BRIN, 2003)
Paleolithic tools such as those found in the river flow in the Serayu Mountains environment in the Banyumas Regency area consisting of chopper-chopping tools and flakes. Until now, it is believed that this type of artifact is related to hunting activities and the collection of food. The exact function of each type of paleolithic tools in relation to this activity is not yet known. Based on its size, it is estimated that a large enough tool is used for quite heavy work such as cutting and splitting objects that are quite hard. Meanwhile, the tools that are relatively small and thin are used for cutting and slicing objects that are quite soft. It is possible that the paleolithic tools did not function specifically but were multi-functional. Besides directly functioning as tools for hunting, gathering and processing food, these tools are also used to make other tools from different materials, such as wood or bamboo for example.